Studies of antithyroid antibodies in Down's syndrome - B. J. Schmidt; S. Piva; A. L. O. Schalch; C. Ortega; M. M. Sousa; D. B. Torres; S. Krynski (Arquivos de Neuro-Psiquiatria)
The presence of antithyroid antibodies (antithyroglobulin and antimicrosomal) in the serum of patients with Down's syndrome and their respective mothers were studied based on data from the literature, showing a possible correlation between the presence of these antibodies in the serum of mothers and the birth of mongoloid children. Antithyroid antibodies were studied in 40 patients with Down's syndrome, with ages ranging from 5 months to 21 years old, 24 males and 16 females and in the respective mothers whose ages varied from 22 to 66 years. In none of the analyzed sera of the mongoloids as well of their mothers, the authors were able to detect the antithyroid antibodies studied.